Chromosome numbers for the Italian flora: 4 - Lorenzo Peruzzi; Raquel Chiavegatto; Marco D'Antraccoli; David Dolci; Francesco Roma-Marzio (Italian Botanist, 2017)
In this contribution new chromosome data obtained on material collected in Italy are presented. It includes 9 chromosome counts for Polygala (Polygalaceae), Dianthus and Silene (Caryophyllaceae).